Peningkatan Produksi Bawang Merah dengan Agihan Cendawan Mikoriza Arbuskular dan Cu pada Lahan Gambut - Murniati '; Arnis En Yuliana; Fetmi Silvina (Jurnal Sagu, 2008)
Peat soil is potential for growing shallot but there is some constraints to produce good yields. This research aimed to know effect of CMA and Cu on the growth and production of shallot. This research was conducted in field laboratory Faculty of Agriculture, University of Riau, Rimbo Panjang, Kampar. The treatments were arranged in a factorial 3x4 in Randomized Block Design (RBD) with three replications. CMA (0,10 and 20 gram.plant-1) was the first factor and Cu (0,5,10 and 15 kg.ha-1 provided the highest result.